2011
DOI: 10.1080/19315864.2011.595535
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity in Adolescents and Young Adults With Autism

Abstract: This article reports the findings of a study investigating rates and types of comorbid mental disorder evident in adolescentsand young adults with autism. A sample of 84 young people ( M = 19.5 years, SD = 4.6) with Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision (DSM-IV-TR; American Psychiatric Association, 2000) autistic disorder participated in the study. Comorbid mental disorder was assessed through a semistructured comprehensive clinical interview with all participants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…Understanding comorbid mental health problems is important not only because of the high prevalence but also because of the impact on daily functioning, long-term prognosis, and the added burden and challenges faced by individuals and their families. Individuals with ASD have higher rates of comorbidity compared to the general population (Ghaziuddin et al 1998;Moseley et al 2011), a psychiatrically referred population of youth without ASD (Joshi et al 2010), as well as individuals with ID alone (Bradley et al 2004;Brereton et al 2006;LoVullo and Matson 2009), although the latter has not been consistently found (Tsakanikos et al 2006). The most commonly reported psychiatric disorders include anxiety and depression (MacNeil et al 2009;Sterling et al 2008;White et al 2009).…”
Section: Prevalence Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding comorbid mental health problems is important not only because of the high prevalence but also because of the impact on daily functioning, long-term prognosis, and the added burden and challenges faced by individuals and their families. Individuals with ASD have higher rates of comorbidity compared to the general population (Ghaziuddin et al 1998;Moseley et al 2011), a psychiatrically referred population of youth without ASD (Joshi et al 2010), as well as individuals with ID alone (Bradley et al 2004;Brereton et al 2006;LoVullo and Matson 2009), although the latter has not been consistently found (Tsakanikos et al 2006). The most commonly reported psychiatric disorders include anxiety and depression (MacNeil et al 2009;Sterling et al 2008;White et al 2009).…”
Section: Prevalence Ratesmentioning
confidence: 99%
“…In terms of quality of adult life, there is increasing evidence suggesting that comorbid psychiatric symptoms and disorders are common in individuals with ASD, with estimated rates ranging from 30% to 70% (e.g., Bradley et al 2004;Gjevik et al 2011;Leyfer et al 2006;Moseley et al 2011;Simonoff et al 2008;Skokauskas and Gallagher 2010). Understanding comorbid mental health problems is important not only because of the high prevalence but also because of the impact on daily functioning, long-term prognosis, and the added burden and challenges faced by individuals and their families.…”
Section: Prevalence Ratesmentioning
confidence: 99%
“…Although previous studies demonstrated a wide range (0% to 28%) of lifetime prevalence of schizophrenia in ASD subjects [8,35,36,38,41,43,[48][49][50], most of them reported a prevalence of under 4% [8,35,36,41,43,[48][49][50]. Neurocognitive impairments such as executive dysfunction [51] and deficits in theory of mind [52] in subjects with ASD are considered a vulnerability for future psychosis according to studies on prodromal psychosis [53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, children [6] and adults [7] with ASD have many other psychiatric disorders. One study indicated that young people with ASD are 2 to 4 times more likely to experience comorbid mental disorders than control subjects of the same generation [8]. The mean number of lifetime psychiatric comorbidities were also greater in individuals with ASD than in those without ASD at both young [9] and adult ages, that is, 6.0 ± 3.4 for subjects with ASD versus 3.5 ± 2.7 for those without ASD [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation